Kink and everyday life : interdisciplinary reflections on practice and portrayal - Hart, Kylo-Patrick R.; Cutler-Broyles, Teresa (Emerald interdisciplinary connexions, 2021)
The term 'kink' evokes a variety of cultural responses ranging from curiosity and arousal to disgust and fear. Many of these responses are based on assumptions about its practices and participants, due to often inaccurate and ever-more-frequent representations in popular culture. These selected authors challenge those assumptions and emphasize how a number of non-normative sexual activities and ways of being can be empowering and liberating rather than deleterious or 'deviant', helping to bring the world of kink out of the shadows. They illuminate past and present kinky phenomena by exploring BDSM, experimentation, fetishism, gender bending, performativity, and sexual role-playing, as experienced in a variety of domains and represented in literature, film, and television. Contributing to revised notions of inclusivity and acceptance, this interdisciplinary work deftly identifies both historical and current approaches to understanding and analyzing kink, and pinpoints avenues for future research. It is an important addition to the emergent areas of BDSM and kink studies.